Uses and potential of socio-technical mobile information and communication devices in French-speaking sub-Saharan Africa : case of two towns in Niger, Niamey and Maradi - (:unkn) unknown (My University, 2021)
This research focuses on the "uses and potentialities of mobile socio-technical information and communication devices (DISTIC) in sub-Saharan Francophone Africa. Case of two regions of Niger: Niamey and Maradi. It aims to analyze the uses and appropriation of cell phones (ordiphone and smartphone), computers, digital tablets, the Internet and digital networks (platforms, social networks, application, etc.) in the context of socio-economic and professional development and information culture (or digital culture). It is in line with the work carried out on the acculturation of technology. It essentially integrates the issue of development with digital media and is also inspired by work in the sociology of innovation, uses, appropriation, dissemination, but especially the social insertion of digital tools in the daily practices of African users. She will build her theoretical framework taking into account the contributions of Nora Quebral for the communication for socio-economic development. The concept of "capability" developed by Amartya Sen is very relevant in the context of a developing country.Over the past 30 years, Information and Communication Technologies (ICT) have experienced unprecedented development in both developed and developing countries. They have become a "new vector" that is increasingly indispensable for economic growth and have transformed the planet into a small digital village. These ICTs, and mainly mobile DISTICs, have changed the behavior of the workforce. The combination of computing and telecommunications has unquestionably made it possible to collect, process and circulate information around the world - in real time. Indeed, in an international context dominated by the "technological revolution" as symbols of modernity and factors of integration into the world economy, the major challenges of globalization increasingly impose the need for each country to integrate harmoniously into the "information society", or now the new bu
Keywords: African Research